The equation is (x - 1)*(x - 3) = 0 or x2- 4x + 3 = 0The equation is (x - 1)*(x - 3) = 0 or x2- 4x + 3 = 0The equation is (x - 1)*(x - 3) = 0 or x2- 4x + 3 = 0The equation is (x - 1)*(x - 3) = 0 or x2- 4x + 3 = 0
The roots of the equation are -4 and 3. Simplest solution is (x +4 )(x - 3) which multiplies out as x^2 + x - 12 = 0
There are 2 (main) ways you can find the solution to a quadratic equation:Factorisation: If you take, for example, the equation (x-3)(x-2) = 0. Either (x-3) or (x-2) must equal 0 for the equation to be true: you then have x-3 = 0 (i.e. x = 3) and x-2 = 0 (i.e. x = 2). These are your solutions to the equation. If you have an equation in the form (say) x2+x-12 = 0, you can find that this is equivalent to (x-3)(x+4) = 0, so x = 3 or x = -4.The magic formula: If the equation won't factorise, or you can't see how it would, there is a formula you can use to give you both values of x: for any equation ax2+bx+c = 0, x = (-b±√(b2-4ac))/2a. The two values of x come from the ±: one uses a plus and the other a minus.
A solution to an question makes the equation true. For example a solution to the equation 3x = x + 6 is x = 3, since 3(3) = 3+6.
X2 - X - 6 = 0what two factors of - 6 add up to - 1 ?(X + 2)(X - 3)============(- 2, 0 ) and (3, 0 )------------------------------solution set of points
How about x+4 = 0 ?
Here is an example: x + 5 = 5If you subtract five from both sides, you get x = 0, which is an example of getting 0 as a solution for an equation.
Only a linear equation in one variable x , which is an equation of the form ax + b = 0, (where a is different than 0), has only one solution. The solution is: x = -b/a
It is a linear equation in x. The equation has the solution x = 0.
Because without an equality sign it can not be considered to be an equation and therefore has no solution.
x = 00 reduces to x = 0/0. Both are undefined, and thus cannot be considered "equal". Other than that, nothing.